1971
DOI: 10.1099/00207713-21-1-25
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas shigelloides (Bader) Ewing et al.: a Proposal That It Be Transferred to the Genus Vibrio

Abstract: A comparison of the data now available on the microorganism variously called C27, Aeromonas shigelloides, Pseudomonas shigelloides, Pseudomonas mich igan i, Plesiomonas sh igelloides, and Fergusonia shigelloides suggests that this organism fits best into the generic description of Vibrio and accordingly should be transferred to this genus as Vibrio shigelloides (Bader) comb. nov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1972
1972
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Various investigators differ in their opinion regarding the classification of strains tentatively identified as A. shigelloides. Ewing et al (3) consider that these strains represent a species belonging to the genus Aeromonas of the family Pseudomonadaceae; Habs and Schubert (5) suggest that they belong to a newly proposed genus (Plesiomonas) of the same family, whereas Hendrie et al (6) propose that the strains be classified as members of the genus Vibrio belonging to the family Spirillaceae. At this time, therefore, the classification of these strains is still in doubt.…”
mentioning
confidence: 99%
“…Various investigators differ in their opinion regarding the classification of strains tentatively identified as A. shigelloides. Ewing et al (3) consider that these strains represent a species belonging to the genus Aeromonas of the family Pseudomonadaceae; Habs and Schubert (5) suggest that they belong to a newly proposed genus (Plesiomonas) of the same family, whereas Hendrie et al (6) propose that the strains be classified as members of the genus Vibrio belonging to the family Spirillaceae. At this time, therefore, the classification of these strains is still in doubt.…”
mentioning
confidence: 99%
“…Several Vibrio strains have also been found to be ECA negative. In contrast, bacteria variously classified as Plesiomonas or Aeromonas or Vibrio shigelloides (46,69,76) are ECA positive. The specific name shigelloides refers to antigenic cross-reactivity with Shigella sonnei, which seems to involve the 0 antigen (46).…”
Section: Mannua-containing Bacterial Antigensmentioning
confidence: 92%
“…The temperature range for P. shigelloides growth is between 8 and 44°C, while optimal growth occurs in the range of 37-38°C [7,8]. Due to a specific phenotype, the bacterium has been renamed several times: C27 (1947) [9], Pseudomonas shigelloides (1954); Escherichia sonnei (1956); Pseudomonas michigani (1959), Aeromonas shigelloides; Pleisomonas shigelloides (1960); Fergusonia shigelloides (1963); Scatomonas michigani (1964), Vibrio shigelloides (1971) [10,11] and Proteus shigelloides [12]. For a long time, it was classified as a member of the family Vibrionaceae, along with Aeromonas, as they share many phenotypic features.…”
Section: Introductionmentioning
confidence: 99%